Future desire for children among women living with HIV in Atlanta, Georgia. Issue 4 (2nd April 2016) - Haddad, Lisa B.; Machen, Leah Kathleen; Cordes, Sarah; Huylebroeck, Brian; Delaney, Augustina; Ofotokun, Igho; Nguyen, Minh Ly; Jamieson, Denise J.
ABSTRACT: Little is known regarding family planning desires among women living with HIV in the United States. This study aimed to identify factors influencing desire for children in the future among HIV-infected women in Atlanta, Georgia. HIV-infected women ages 18–45 completed an ACASI (audio computer-assisted self-interview) questionnaire. Chi-square, t -tests, and multivariate logistic regression evaluated factors associated with desire for future children. Of 181 participants, 62 (34.3%) expressed desire for children in the future, with increased desire among younger women (age <26) and those with seronegative partners. Concerns for horizontal and vertical HIV transmission were deterrents to future childbearing. Condom use and overall knowledge of transmission risk was low. Over a third of women desiring a child never discussed their desire with a physician. Misinformation regarding HIV transmission risks persists and is a notable concern influencing desire for children. Providers should reassess family planning desires regularly through integrated HIV care.